Development of an LC-MS/MS method for the quantitation of deoxyglycychloxazol in rat plasma and its application in pharmacokinetic study - Rongshan Li; Ruixue Ran; Quansheng Li; Yurong Huang; Yuan Gu; Duanyun Si (Elsevier, 2016)
Deoxyglycychloxazol (TY501) is a glycyrrhetinic acid derivative which exhibits high anti-inflammatory activity and reduced pseudoaldosteronism compared to glycyrrhetinic acid. In this study, a sensitive and rapid liquid chromatography-tandem mass spectrometry (LC-MS/MS) method was established for the quantitation of TY501 in rat plasma. Plasma samples were treated by precipitating protein with methanol and supernatants were separated by a Symmetry C8 column with the mobile phase consisting of methanol and 10 mM ammonium formate (containing 0.1% of formic acid) (90:10, v/v). The selected reaction monitoring (SRM) transitions were performed at m/z 647.4→191.2 for TY501 and m/z 473.3→143.3 for astragaloside aglycone (IS) in the positive ion mode with atmospheric pressure chemical ionization (APCI) source. Calibration curve was linear over the concentration range of 5-5000 ng/mL. The lower limit of quantification was 5 ng/mL. The mean recovery was over 88%. The intra- and inter-day precisions were lower than 6.0% and 12.8%, respectively, and the accuracy was within ±1.3%. TY501 was stable under usual storage conditions and handling procedure. The validated method has been successfully applied to a pharmacokinetic study after oral administration of TY501 to rats at a dosage of 10 mg/kg.